Caixabank's Takeover of BPI: the impact on BPI's stock - Jesus, João Pereira Pedro de (2019)
Caixabank, the Spanish bank that belongs to the "La Caixa" financial group, has been BPI's shareholder for more than twenty years and since 2015 it has tried to take over the Portuguese bank. The ultimate takeover bid was in January 2017 and Caixabank became BPI's majority shareholder in February 2017. This thesis main objective is to study the impact this takeover had on BPI's security, focusing on measuring the unexpected performance of the stock. Thus, we applied the event study methodology, using the market model as estimation model and choosing an estimation and event window that better fitted the corresponding event. We computed the abnormal returns for the event window days and evaluated if these returns were statistically significant, presenting the main findings obtained. This thesis outcome reveals that the takeover had a negative impact on BPI's security price, which was statistically significant on the day of the takeover and the following day. Moreover, we observed the takeover had an unfavorable effect for the stock, which ended up being excluded from the PSI 20 index.